O(s) sujeitos no Clube da Luta : o outro no mesmo - Lunkes, Fernanda Luzia (2007)
In this research we lean over the subject's category on the filmic production. We have as goal to explicit the constitution processes of the subjects in the movie Fight Club, an American production released in 1999. In the Analysis of the Discourse perspective (Pêcheux, Orlandi), the subject's homogeneity is an ideological effect. And one of the "surprises" of the movie is just the fact that the spectator finds out, in the end, that the two characters, Jack and Tyler, are the same person. And in this way, the body materializes itself. Our reading acts walk on the direction of showing through the scenes from which we selected the cuts the questions that we made ahead of our objective, in view that the body is in all filmic narrative either as repetition place either as resistance place: if it has an imaginary constantly interpellating, can the body be a place to bring, on certain form, this imaginary? Through the description of these subjects' discoursivity, trying to show them heterogeneous construction, that leads us to consider the production conditions, here taken as the discourses about the post-modern and about the subject category; the discourses that circulate around the cinema, about the movie Fight Club; the scenes from which we selected the cuts. The fragments were made according to the questions that motivated us, not implying, because of this, a division between the verbal and the not verbal. We took both symbolic instances as discourse. We undertook our analysis segregating Jack and Tyler not as empirical subjects but as speaking subjects, showing the coercions that the subject goes through and how this occurs in the symbolic through the social imaginary that interpellates it. We consider that our subject goes constituting himself for different processes of identification in the body. In the first phase his name is silenced, while it has a regularity in nominating brands, as the metaphor of the accepted body; in the second, in another metaphor, he calls himself "something" of Jack, approaching since his biological until his emotional side; and the third, through Tyler, when he brings one another discoursivity, his Other, one speech of resistance for the body with other marks. That doesn't lead us to think that he escapes to another ideology. To resist, yes. To run away, never. We understand that the title Fight Club can be organized as a discursive paraphrase, where "fight" means "physical fight", but also points to more than one meaning: means "ideological fight". And body being both discoursivities. Our study, more than answers, intends to raise questions that, possibly, will generate others. How desiring subjects, we don't talk about conclusions, but reading actions, these inserted in the movement of the speech, that escapes from us.